A Novel Approach in Heptapartitioned Neutrosophic Sets with its Weighted Arithmetic Averaging Operator - Sudharani R; Chitra Devi D; Mahimairaj P; Thirunavukkarasu J; Jeyanthi L; Nagalakshmi T (Neutrosophic Sets and Systems)
The aim of this paper is to introduce the heptapartitioned neutrosophic weighted arithmetic averaging operator and also some of its basic algebraic properties of heptapartitioned neutrosophic set. A score and accuracy function of heptapartitioned neutrosophic set has been established. With the proposed score function, accuracy function and averaging operator a multicriterion decision making problem has been solved and ranked with their alternatives by using TOPSIS technique with different weightages which has been compared with the MOORA method.